Current Bioengineering Methods for Whole Kidney Regeneration - Shuichiro Yamanaka; Takashi Yokoo (Stem Cells International)
Kidney regeneration is likely to provide an inexhaustible source of tissues and organs for immunosuppression-free transplantation. It is currently garnering considerable attention and might replace kidney dialysis as the ultimate therapeutic strategy for renal failure. However, anatomical complications make kidney regeneration difficult. Here, we review recent advances in the field of kidney regeneration, including (i) the directed differentiation of induced pluripotent stem cells/embryonic stem cells into kidney cells; (ii) blastocyst decomplementation; (iii) use of a decellularized cadaveric scaffold; (iv) embryonic organ transplantation; and (v) use of a nephrogenic niche for growing xenoembryos for de novo kidney regeneration from stem cells. All these approaches represent potentially promising therapeutic strategies for the treatment of patients with chronic kidney disease. Although many obstacles to kidney regeneration remain, we hope that innovative strategies and reliable research will ultimately allow the restoration of renal function in patients with end-stage kidney disease.